FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN-PERUSAHAAN GO PUBLIC DI BEJ - Reni Yendrawati; Fandli Rokhman (University of Merdeka Malang, 2008)
Timeliness represented a very important matter in determining financial statementvalue. This research was purposed to investigate the influence of audit delay factors, namelycompany size, company that announced loss, level of company profitability, auditors opinionand industrial sector. Audit delay could affect the timeliness of accounting information releases,and it would be known that timeliness was associated with the market reaction to theinformation released. Sampels were selected by method of purposive sampling. Regressionanalysis was used to investigate audit delay factors. The results could be interpreted thataudit delays tended to be longer for the company that announced loss in non-manufacturessampel, auditors opinion in overall sampel and auditors opinion in non-manufactures sampel.